Timely Meditations: Martin Heidegger and Postmodern Politics - Leslie Paul Thiele (Princeton University Press, 2014)
STRANGE INDEED IS the upright walker. With grasping hands and forward- looking eyes, this most wondrous of creatures has developed the sentiment, thought, speech, and craft needed to extend its reign across the expanse of the earth and beyond. What are the limits to its power? The ancients presumably had their answer. "Do not seek to be master in every way," Creon had warned Oedipus. But Creon, we know, would not follow his own advice. He met a fate no less dire than that of the former king of Thebes. Any human pursuit that ignores limitations, Sophocles suggests, inevitably brings doom. Well or ill may come of our vast ingenuity. With tragic closure the chorus insists that "our happiness depends on wisdom all the way." Contemporary liberalism easily marks the limits Creon transgressed in his patriarchal and authoritarian pursuit of power. From the perspective of this hegemonic ideology of our era, the young Antigone appears as the courageous voice of individual liberty. Creon rules as the despot blinded to the inalienability of this liberty by the arrogance of power. But justice prevails, and tyranny brings calamity to both king and kin. The sentiments that allowed the city to form are vindicated. Surely this interpretation is an anachronistic imposition. Nevertheless, liberalism may rightly claim to have forged many of the needed restraints for despotic power in the modern world. And surely this is no small feat. Of late, however, in the midst of its most glorious, global vindications, liberalism has been challenged anew and from within Its very success in valorizing individual liberty has potentially undermined both the sentiments needed to sustain political community and the wisdom needed to restrain the cumulative craft, consumption, and propagation of billions of individuals who are wearing away the earth. It is, I believe, an open question whether some form of liberalism can cultivate these sentiments and this wisdom. What is not m question is the need for such cultivation.